2008
DOI: 10.5005/jcdp-9-7-17
|View full text |Cite
|
Sign up to set email alerts
|

The Environmental Influence of Light Coke™, Phosphoric Acid, and Citric Acid on Elastomeric Chains

Abstract: Aim:The purpose of this study was to evaluate the in vitro effect of Light Coke™, phosphoric acid, and citric o acid on the force decline pattern of two types of elastomeric chains. Methods and Materials:One hundred sixty gray colored elastomeric chain modules, 80 Chainette (GAC) and 80 Sunburst™ (GAC) chains, were divided into four groups for immersion into Light Coke, phosphoric acid, citric acid, and artificial saliva. The initial stretched force of the elastomeric chains ranged from 220gf to 250gf. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 12 publications
3
22
0
3
Order By: Relevance
“…Nevertheless, these materials are not considered ideal, as the force they generate diminishes gradually during the activation period. 12,13 Therefore, various studies 3,[8][9][10][11] have sought to establish the mechanical and environmental factors that contribute to the force degradation of different orthodontic elastics. Mouthwashes are commonly used by orthodontic patients; thus, it is vital to investigate how mouthwashes affect orthodontic devices.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these materials are not considered ideal, as the force they generate diminishes gradually during the activation period. 12,13 Therefore, various studies 3,[8][9][10][11] have sought to establish the mechanical and environmental factors that contribute to the force degradation of different orthodontic elastics. Mouthwashes are commonly used by orthodontic patients; thus, it is vital to investigate how mouthwashes affect orthodontic devices.…”
Section: Discussionmentioning
confidence: 99%
“…In their in-vitro study, Kim et al [13] recorded significantly lower forces with pre-stretched five and six-modular PCs than in a non-pre-stretched control group. There is also evidence that a drop in the level of force may ensue during the regular period of application of elastomeric chains, which can be up to 4 weeks [11,23,24,28]. By contrast, PC geometry and various manufacturing techniques appear to have no influence on the force delivered [3,8].…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [13] konnten in einer Invitro-Untersuchung bei vorgedehnten fünf-und sechsmoduligen PCs signifikant geringere Kräfte ermitteln als in einer nicht vorgedehnten Kontrollgruppe. Zudem wurde festgestellt, dass während der regulären Applikationsdauer elastomerer Ketten, die bis zu 4 Wochen betragen kann, mit einer Abnahme des Kraftniveaus zu rechnen ist [11,23,24,28]. Die Geometrie der PCs sowie verschiedene Fertigungstechniken scheinen hingegen keinen Einfluss auf die abgegebene Kraft zu haben [3,8].…”
Section: Introductionunclassified
“…Moreover, the oral cavity's moist environment exerts an influence on the PCs' force levels [9], and PCs in the mouth are subjected to pH variations during the ingestion of liquid and solid foods. Teixeira et al [23] observed no influence of Coke Light, phosphoric acid, citric acid, or artificial saliva on the force level. In contrast, in a study by Ferriter et al [8], a slightly alkaline environment (pH = 7.26) during a 4-week observation period led to a greater drop in force than the pH value found in plaque (pH = 4.95).…”
Section: Introductionmentioning
confidence: 99%
“…Zusätzlich sind die Ketten in der Mundhöhle während der Aufnahme von flüssiger oder fester Nahrung pHWert-Schwankungen ausgesetzt. Teixeira et al [23] …”
Section: Introductionunclassified